Parmotrema species in a cloud forest region turned into an urban zone in Xalapa, Veracruz, Mexico - Pérez-Pérez, Rosa Emilia; Guzmán, Gastón (Bosque (Valdivia), 2017)
The cloud forest of Mexico has the highest biodiversity among the country's diverse forest types; however, 90 % of the cloud forest ecosystem in the region of Xalapa has been destroyed and what remains is at risk. This region is home to an enormous diversity of lichen species. In a lichen survey carried out in this remnant of cloud forest in Xalapa, which has been turned into an urban area, we identified only eight species of Parmotrema, all of which showed vegetative propagules. Regardless of the role of the genus in the ecosystems, these lichens may be disappearing as a result of the transformation and destruction of the cloud forest ecosystem in Mexico.